CD5‐expressing CD8+ T‐cell subsets differ between children with type 1 diabetes and controls. Issue 10 (18th July 2021) - Wadenpohl, Josefine; Seyfarth, Julia; Hehenkamp, Paul; Hoffmann, Maximilian; Kummer, Sebastian; Reinauer, Christina; Döing, Carsten; Förtsch, Katharina; Mayatepek, Ertan; Meissner, Thomas; Jacobsen, Marc
Abstract: Different lymphocyte subsets are involved in autoimmune pathogenesis of type 1 diabetes (T1D). Previous studies suggested a role of CD5‐expressing T and B cells including rare unconventional lymphocytes with combined T‐ and B‐cell features [dual expressing (DE) cells]. We performed algorithm‐supported multiparameter flow cytometry and quantitative PCR to investigate immune cell subsets and DE cells in children with T1D ( n = 20) and matched controls ( n = 20). Comparisons of conventional immune cells detected increased proportions of CD3 + T cells in T1D patients, whereas CD19 + B‐cell proportions were comparable to controls. Self‐organizing maps for flow cytometry analyses (FlowSOM) showed highly similar CD5‐expressing B‐cell subsets and no differences for DE cells were detected between the study groups by flow cytometry or specific quantitative PCR. Notably, differences in CD8 + T cells were indicated by FlowSOM and similarity‐based t‐distributed stochastic neighbor embedding (tSNE) analyses. Study group comparisons confirmed significantly reduced CD8 + T‐cell proportions with moderate or low CD5 expression in T1D patients. Finally, in vitro experiments showed stable CD5 expression differences of CD8 + T cells after T‐cell activation, cytokine stimulation and culture. We observed differences of T‐cell coreceptor CD5 expression in T1D patients with potential relevance for immune regulation of CD8 + T‐cell activation. Abstract : We performed algorithm‐supported analyses of multiple B‐ and T‐cell molecules by flow cytometry in study groups of children with type 1 diabetes and matched controls. Complexity reduction tools showed high similarity of B‐cell and dual expressing subsets between the study groups but self‐organizing map (FlowSOM) software identified novel CD8 + T‐cell populations with aberrant CD5 expression. Type 1 diabetes patients had lower proportions of CD8 + T cells with low or moderate CD5 expression and in vitro experiments indicated persistence and functionality of this novel immune cell subsets.